Thermodynamic Stability of Ettringite Formed by Hydration of Ye’elimite Clinker - Marcela Fridrichová; Karel Dvořák; Dominik Gazdič; Jana Mokrá; Karel Kulísek (Advances in Materials Science and Engineering)
In order to save limited natural resources by utilising industrial by-products, this paper focuses on an entirely new application of fluidized bed combustion fly ash (FBCFA) into Portland composite cements. It is not currently used because undesirable ettringite, 3CaO·Al2O3·3CaSO4·32H2O, is formed during the hydration of FBCFA. Although the stability of ettringite has been the subject of much research, the solution is not yet fully clear. Ettringite is generally considered to be stable up to a temperature of 110°C; however, some investigators claimed that ettringite may already decompose at even ambient temperatures. To prove these statements, ettringite was prepared by the hydration of ye’elimite, 3CaO·3Al2O3·CaSO4, and the system stored at laboratory temperature in two environments: in laboratory settings and in an environment of saturated water vapour. The mineralogical composition of ettringite was long term (up to 160 days of hydration) and was analysed by X-ray diffraction (XRD) and differential thermal analysis (DTA). The hydration of ye’elimite is a relatively complex process. Only approximately 30% of ettringite was formed under laboratory conditions that appeared to gradually convert into metaettringite. Within an environment of saturated water vapour, we observed the conversion of ettringite into monosulfate. Original ye’elimite was indicated as the dominant phase of both storages.